Recent advances in patient selection and devices for transcatheter edge-to-edge mitral valve repair in heart failure. (1st February 2020) - Orban, Martin; Lüsebrink, Enzo; Braun, Daniel; Stocker, Thomas J.; Bagaev, Erik; Hagl, Christian; Näbauer, Michael; Massberg, Steffen; Orban, Mathias; Hausleiter, Jörg
ABSTRACT: Introduction : Secondary mitral regurgitation (MR) is a consequence of chronic heart failure (HF) with reduced left ventricular ejection fraction (HFrEF) and left ventricular (LV) dilatation. Severe MR worsens prognosis and accelerates LV dilatation as well as decline in LV ejection fraction. Areas covered : In this review we summarize the available data of patients with chronic HF undergoing transcatheter edge-to-edge mitral valve repair (TMVR) with the MitraClip system for severe secondary MR, considering also results of recent MITRA-FR (Multicenter Study of Percutaneous Mitral Valve Repair MitraClip Device in Patients With Severe Secondary Mitral Regurgitation) and COAPT (Cardiovascular Outcomes Assessment of the MitraClip Percutaneous Therapy for Heart Failure Patients With Functional Mitral Regurgitation) trials. Furthermore, we discuss recent advances in devices for TMVR, focussing on the new MitraClip XTR as well as the Edwards PASCAL system. Expert opinion : Optimal patient selection for TMVR is still a matter of great debate due to contradictory results of MITRA-FR and COAPT. New edge-to-edge devices (MitraClip XTR and Edwards PASCAL) come with longer clip arms and the Edwards PASCAL system is the first device with the capability of independent grasping of anterior and posterior leaflet, providing interventionalists with more options to treat patients with secondary MR.